2007
DOI: 10.1016/j.nurt.2007.07.004
|View full text |Cite
|
Sign up to set email alerts
|

Chemokines and Chemokine Receptors in Neurological Disease: Raise, Retain, or Reduce?

Abstract: Summary:Chemokines and chemokine receptors comprise a large number of molecules implicated in a wide range of physiological and pathological functions. Numerous studies have demonstrated the roles of chemokines and chemokine receptors: 1) during development, by regulating hematopoiesis, cardiogenesis, and vascular and cerebellar development; 2) during tumor biology, by controlling cell proliferation, angiogenesis, and metastasis; and 3), especially during leukocyte migration, by acting on firm adhesion, locomo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
126
0
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 155 publications
(129 citation statements)
references
References 86 publications
1
126
0
1
Order By: Relevance
“…The target of CCL2, involved in mediating the neuroprotective activity of the chemokine, has not been addressed in the present study: previous reports showed that the main receptor for CCL2 is CCR2, but this chemokine can also bind to other receptors like CCR1, CCR4, and L-CCR, albeit with lower affinity Savarin-Vuaillat et al, 2007;White et al, 2007;Quinones et al, 2008). In addition, CCR2 expression in brain parenchyma is controversial.…”
Section: Discussionmentioning
confidence: 86%
“…The target of CCL2, involved in mediating the neuroprotective activity of the chemokine, has not been addressed in the present study: previous reports showed that the main receptor for CCL2 is CCR2, but this chemokine can also bind to other receptors like CCR1, CCR4, and L-CCR, albeit with lower affinity Savarin-Vuaillat et al, 2007;White et al, 2007;Quinones et al, 2008). In addition, CCR2 expression in brain parenchyma is controversial.…”
Section: Discussionmentioning
confidence: 86%
“…Exogenous FGF caused a 62% increase in the overall number of dividing cells (10). SDF-1␣ and its G protein-coupled receptor CXCR4 are also implicated in cardiogenesis (25). Aurora B kinase is a key regulator of chromosome segregation during mitosis (11).…”
Section: Discussionmentioning
confidence: 99%
“…These secreted inflammatory mediators, in turn, activate more microglia and astrocytes to produce inflammatory molecules. In addition, immune cells including, T cells, B cells and monocytes are found to migrate from the periphery through the BBB and present in the brains of AD individuals (Conductier et al 2010;Ruan et al 2010;Savarin-Vuaillat and Ransohoff 2007).…”
Section: Inflammation In Admentioning
confidence: 99%